Neoplastic transformation of mouse mammary epithelial cells by in vitro exposure to N-methyl-N-nitrosourea. - Miyamoto, S (1988)
High-efficiency neoplastic transformation of mouse mammary epithelial cells in primary collagen gel culture was induced by N-methyl-N-nitrosourea (MNU). Mammary epithelial cells, isolated from virgin BALB/c mice, were embedded within collagen gels and grown in a serum-free medium containing prolactin, progesterone, and linoleic acid. The cells were then treated with MNU on day 3 of culture and subsequently at weekly intervals for up to 4 weeks. Eleven to 14 days after the final carcinogen treatment, the cells were removed from the collagen gels and injected into the cleared mammary fat pads of syngeneic hosts to assay for transformed cell populations. A single exposure or multiple exposures of these cells to MNU was effective in inducing tumorigenic cells that produced palpable tumors as early as 6 weeks after transplantation. Two treatments with MNU (100 micrograms/ml) were optimal for neoplastic transformation and produced tumors in 79% of the injected fat pads. All the tumors originated at the site of injection and had extensive central necroses. Histological examination indicated that the tumors were mammary carcinomas. Secondary transplantation of tumor pieces into intact mammary glands produced palpable carcinomas of the same histology within 1-8 weeks. Control cells cultured for the same periods of time as MNU-treated cells produced only ductal outgrowths that were morphologically similar to those found in the mammary glands of adult virgin hosts. This system provides a distinct means to study the mechanism of mammary neoplastic transformation at cellular and molecular levels.